Effect of Advanced Yogasanas on Psycho-Biochemical Parameters in Adults: A Prospective Non-Randomized Single Arm Trial - Chanchal Vijay; Khushbu Jain (Tehran University of Medical Sciences, 2024)
In the research investigation exploring the effects of Advanced Yogasanas on psycho-biochemical parameters, a cohort of 67 adult yoga practitioners, spanning ages 20 to 54 (with a mean age of 28.94±6.95), actively engaged in an extensive one-month training program facilitated by certified yoga instructors. The sessions were conducted during evening hours, specifically from 4 to 7 pm, ensuring a consistent and structured learning environment. To evaluate the psychological impact, participants underwent assessments employing The Mindful Attention Awareness Scale (MAAS) for Attention and the Self-Efficacy Scale for Self-efficacy. The outcomes revealed remarkable improvements in Attention scores (p<0.01**) and Self-efficacy scores (p<0.01**), highlighting the positive influence of advanced yogasanas on these crucial psychological parameters. Turning to the realm of biochemical parameters, the gathered data indicated non-significant alterations in total cholesterol (md=1.65); while there was a notable decrease in triglycerides (md=0.917). Additionally, high-density lipoprotein exhibited an increase (md=1.636), accompanied by reductions in both low-density lipoprotein (md=0.858) and very low-density lipoprotein (md=0.358) between the pre- and post-assessment periods. These findings collectively underscore the beneficial impact of a one-month regimen of yogasanas on a spectrum of psychological and biochemical parameters. By emphasizing the holistic advantages, the study advocates for the integration of advanced yogasanas practice, into the daily routines of adults, showcasing the potential for a comprehensive approach to well-being through the incorporation of these advanced yoga practices.